Recent Advances in Dam Engineering - Asthana, B.N.; Khare, Deepak (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book discusses recent developments in dam engineering, covering theoretical as well as practical aspects. The chapters provide detailed descriptions of the types, surveys and investigations, layouts, design, thermal stresses and foundation of dams. The differences between various theories/methods of analysis used in design and their practical application and limitations are clarified. The book focuses on earth fills and landfills and stresses the importance of the foundation treatment. Failure of embankment dams is discussed particularly in the planning and construction stages of the dam. The environmental impact of dams is treated with references to river diversions and reservoir sedimentation. The book is written as a reference book for professional engineers and is also suitable for post graduate courses.
1. Introduction -- 2. Concrete Dams -- 3. Concrete Gravity Dams -- 4. Roller Compacted Concrete Dams -- 5. Embankment Dams -- 6. Earthfill Dams -- 7. Rockfill Dams -- 8. Failure of Embankment Dams -- 9. Foundation Treatment of Dams -- 10. River Diversion -- 11. Hill Slope Stabilization at Dam and Power Projects in Himalayas -- 12. Reservoir Sedimentation -- 13. Instrumentation -- 14. Construction Aspects of Dams -- 15. Dams and Environmental Issues -- 16. Dam Safety.
Keywords: Geotechnical engineering; Engineering geology; Buildings-Design and construction; Environmental sciences-Social aspects; Environmental management; Geotechnical Engineering and Applied Earth Sciences; Geoengineering; Building Construction and Design; Environmental Social Sciences; Environmental Management